Stretchable Polymeric Neural Electrode Array: Toward a Reliable Neural Interface. Issue 1795 (2015) - Guo, Liang
ABSTRACT: Conducting polymers are often employed as coatings on smooth metal electrodes to improve the electrode performance with respect to the signal-to-noise ratio for neural recording, charge-injection capacity for neural stimulation, and inducement of neural growth for electrode-tissue integration. However, adhesion of conducting polymer coatings on metal electrodes is poor, making the coating less durable and the electrical property of the electrode less stable. Moreover, conventional conducting polymers have relative low conductance, preventing their direct use as the electrode and lead material; and they are brittle, making it difficult for flexible neural electrodes to incorporate conducting polymer coatings. We have developed a new polypyrrole/polyol-borate composite film with concurrent excellent electrical and mechanical properties. We further developed a method to fabricate a stretchable multielectrode array using this new material as the sole conductor for both electrodes and leads, in contrast with the conventional approach of incorporating conducting polymers only through coating on non-stretchable metal electrodes. The resulting stretchable polymeric multielectrode array (SPMEA) was stretchable up to 23% uniaxial tensile strain with minimal losses in electrical conductivity. Electrochemical testing revealed the SPMEA's impressive advantage for recording local field neural potentials and for epimysial stimulation of denervated skeletal muscles. As a neural interface engineer, I would also like to compare the compliant neural interfacing technology to other technologies, such as optogenetics, radiogenetics, and even a living neural interface that is currently under development in our lab.